Flow and transmission characteristics of the multistage hydrogen Knudsen pump in the micro-power system. (22nd May 2022) - Lan, Jiang; Xie, Junlong; Ye, Jianjun; Peng, Wenzhu; Jiao, Xiaoyi
Abstract: The multistage hydrogen Knudsen pump based on the thermal transpiration effect has exciting application prospects for hydrogen transport in the micro-power system. The multistage hydrogen Knudsen pump with the silica microchannel is beneficial to its temperature control, which can accurately provide hydrogen transport and storage for the micro-power system. In this paper, the model of the multistage hydrogen Knudsen pump with the silica microchannel is established. The effects of the microchannel height, width and parallel number on the flow and transmission characteristics of the multistage hydrogen Knudsen pump are studied by using the method of N–S equations with the slip boundary. The temperature difference, Knudsen number, thermal transpiration effect, maximum mass flow rate, maximum pressure difference and performance curve under different microchannel parameters are analyzed in detail. The results show that the thermal transpiration effect increases with the microchannel height and decreases with the microchannel width. As the number of parallel microchannels increases, the microchannel is closer to the silicon cantilever, and the thermal transpiration effect becomes stronger. The pumping performance increases with the microchannel height, width and parallel number. The pressurization performance increases with the microchannel height and parallel number. The research results have important guiding significance for the application and design of the multistage hydrogen Knudsen pump in the micro-power system. Graphical abstract: Image 1 Highlights: A multistage hydrogen Knudsen pump model without moving components is proposed. Design and transmission characteristics of multistage hydrogen Knudsen pump are studied. The hydrogen mass flow rate is higher when the microchannel height is higher.